HUMAN RESOURCE QUALITY DEVELOPMENT STRATEGY IN IMPROVING THE COMPETENCE OF GAMBUT TAPE MSMEs IN BANJAR REGENCY SOUTH KALIMANTAN - Diana Hayati; Penta Lestarini Budiati; Dewi Setiawati (Adisam Publisher, 2026)
The Gambut tape industry in Banjar Regency, South Kalimantan, is one of the micro and small businesses that has high economic and cultural potential. However, the competitiveness of this industry still faces various obstacles, including the low quality of human resources, the limited competence of craftsmen, the lack of mastery of production technology, and weak managerial and marketing skills. This research aims to formulate a strategy to improve the quality of human resources in improving the competence of Gambut tape craftsmen so that they are able to increase productivity, product quality, and business competitiveness. This research uses qualitative methods obtained through in-depth interviews, observations, and directed group discussions (FGD) with artisans, local governments, academics and business actors. The results of the study show that improving the quality of human resources through education and training, strengthening technical skills, developing entrepreneurial competencies, utilising digital technology, and strengthening partnership networks can improve the competence of craftsmen. Furthermore, the better competence of craftsmen will improve product quality, business productivity, innovation and competitiveness of the Gambut tape industry. This research is expected to make a theoretical contribution to the development of Human Resource Management studies in the local food-based MSME sector and become the basis for the formulation of local government policies in the sustainable development of the Gambut tape industry.